2018
DOI: 10.1007/s11307-018-1239-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Guidance in Surgical Oncology: Challenges, Opportunities, and Translation

Abstract: Surgical resection continues to function as the primary treatment option for most solid tumors. However, the detection of cancerous tissue remains predominantly subjective and reliant on the expertise of the surgeon. Surgery that is guided by fluorescence imaging has shown clinical relevance as a new approach to detecting the primary tumor, tumor margins, and metastatic lymph nodes. It is a technique to reduce recurrence and increase the possibility of a curative resection. While significant progress has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 180 publications
(207 reference statements)
0
48
0
Order By: Relevance
“…Antigen-specific fluorescent-guided surgery has demonstrated the potential to identify positive tumor margins and metastatic sites of disease in early stage clinical trials. [1][2][3] Although there are many challenges to advancing this promising field, we have focused on antitumor antibody-IR800 probe development to increase tumor accumulation and pharmacokinetic properties. Our previous work with M5A-IRDye800CW showed excellent tumor imaging but with high liver background and relatively fast blood clearance.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigen-specific fluorescent-guided surgery has demonstrated the potential to identify positive tumor margins and metastatic sites of disease in early stage clinical trials. [1][2][3] Although there are many challenges to advancing this promising field, we have focused on antitumor antibody-IR800 probe development to increase tumor accumulation and pharmacokinetic properties. Our previous work with M5A-IRDye800CW showed excellent tumor imaging but with high liver background and relatively fast blood clearance.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Fluorescence-guided surgery (FGS) using tumor-specific antibodies conjugated with near-infrared fluorophores (NIR) have demonstrated the potential to visualize solid tumor lesions in preclinical and early stage clinical trials. [1][2][3] Several commercial cancer therapeutic monoclonal antibodies (mAbs) have been repurposed as molecular optical imaging agents by their conjugation with NIR dyes and are in early-stage clinical trials. [4][5][6] Compared to visible light fluorophores, NIR fluorophores have reduced light scattering, increased depth of penetration, and minimal autofluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, image guided surgery has generated quite a bit of interest in the field of molecular imaging, with several investigators assessing various contrast agents along with various imaging techniques [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Both preclinical and clinical studies have shown the benefits that image guidance can offer during all sorts of surgical applications.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics result in low tumor signal and contrast (Alander et al, ; Schaafsma et al, ; H. Wang et al, ). Therefore, other NIR dyes such as cyanine‐based and novel fluorophores are being investigated for FGS, and seek to improve tumor signal and contrast (Figure ; Hernot, van Manen, Debie, Mieog, & Vahrmeijer, ; Olson et al, ).…”
Section: Image‐guided Surgerymentioning
confidence: 99%